Tingkat Aksesibilitas Pelayanan Air Bagi Masyarakat di Kawasan Padat Penduduk - Dhyah Puspita Dewi; Fadjar Hari Mardiansjah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
The existence of government programs and the existence of a government corporation appointed by the government to provide water to the community is still not enough to meet the needs of clean water. Areas that have been served are still experiencing water access problems. Areas that have not adapted to use other sources using groundwater for personal needs or business, however, it cannot be used forever, so someday they have to switch to water sources provided by the government. On the other hand, lower-middle-income communities are vulnerable to access to water, which concentrated in densely populated and coastal areas, which is difficult for the government to provide access to water services. Therefore, this study wants to show access to water services provided by the government and groundwater supply providers, and how access is received by each community group. The location of this study is in Kemijen Village which the majority consists of the customers of water sources provided by the government and Kampung Tambak Lorok which majority consists of customers of groundwater sources. The results show that groundwater providers provide better access, where lower-middle-class people get lower access than upper-middle-class people.